Raman and surface enhanced Raman spectroscopic investigation on Lamiaceae plants - Rosch, P; Popp, J; Kiefer, W (Journal of Molecular Structure, 1999)
The essential oils of Thymus vulgaris and Origanum vulgaris are studied by means of micro-Raman spectroscopy. The containing monoterpenes can be identified by their Raman spectra. Further the essential oils are investigated in their natural environment, the so-called oil cells of these Lamiacene plants, with surface enhanced Raman spectroscopy (SERS). This method has the advantage to enhance Raman signals and furthermore the SERS effect leads to fluorescence quenching. (C) 1999 Elsevier Science B.V. All rights reserved.
PT: J; SI: Sp. Iss. SI

Raman and surface enhanced Raman spectroscopic investigation on Lamiaceae plants - Rösch, P; Popp, J; Kiefer, W (Journal of Molecular Structure, 1999)
The essential oils of Thymus vulgaris and Origanum vulgaris are studied by means of micro-Raman spectroscopy. The containing monoterpenes can be identified by their Raman spectra. Further the essential oils are investigated in their natural environment, the so-called oil cells of these Lamiaceae plants, with surface enhanced Raman spectroscopy (SERS). This method has the advantage to enhance Raman signals and furthermore the SERS effect leads to fluorescence quenching.
Cited By (since 1996): 13
Keywords: Essential oils; Micro-Raman spectroscopy; Surface enhanced Raman spectroscopy